Heart transplantation and in‐hospital outcomes in adult congenital heart disease patients with Fontan: A decade nationwide analysis from 2004 to 2014. Issue 3 (23rd January 2020) - Hernandez, Gabriel A.; Lemor, Alejandro; Clark, Daniel; Blumer, Vanessa; Burstein, Danielle; Byrne, Ryan; Fowler, Rachel; Frischhertz, Benjamin; Sandhaus, Emily; Schlendorf, Kelly; Zalawadiya, Sandip; Lindenfeld, JoAnn; et al.
Abstract: Introduction: Treatment of adult congenital heart disease patients who require advanced therapies remains challenging due to high perioperative and wait‐list mortality and limited donors. Patients palliated with Fontan are at the highest risk of early mortality due to multiorgan involvement and few centers able to safely transplant them. We sought to evaluate the early outcomes of heart transplants in these adult Fontan patients. Methods: Using the Nationwide Inpatient Sample database, we identified all adults aged at least 18 years old who underwent heart transplantation across U.S. hospitals from 2004 to 2014. We then identified those with specific ICD‐9 codes to include tricuspid atresia, hypoplastic left heart syndrome and common ventricle. Multivariate regression models were created to adjust for potential confounders. Results: A total of 93 Fontan patients underwent heart transplant during the study time (0.5% of all heart transplants). Compared to non‐Fontan heart transplantations, Fontan patients were younger, with a higher incidence of liver disease and coagulopathy. Fontan patients receiving heart transplant had higher mortality during transplant hospitalization compared to non‐Fontan patients (26.3% vs 5.3% OR, 18.10, CI, 5.06‐65.0 P < .001). Extracorporeal membrane oxygenator (ECMO) usage and bleeding were also higher in the Fontan cohort with an OR of 5.30 ( P = .016) and 5.32 ( P = .015) for ECMO and bleeding, respectively. The remaining outcomes were similar for both cohorts. Conclusion: Adults with Fontan palliation undergoing heart transplantation have exceptionally high inpatient mortality, which is nearly five times that of non‐Fontan heart transplant recipients, perhaps related to a delayed referral, surgical complexity, and coexistent, underrecognized liver failure.